2009
DOI: 10.1037/a0014351
|View full text |Cite
|
Sign up to set email alerts
|

Signal detection with criterion noise: Applications to recognition memory.

Abstract: A tacit but fundamental assumption of the Theory of Signal Detection (TSD) is that criterion placement is a noise-free process. This paper challenges that assumption on theoretical and empirical grounds and presents the Noisy Decision Theory of Signal Detection (ND-TSD). Generalized equations for the isosensitivity function and for measures of discrimination that incorporate criterion variability are derived, and the model's relationship with extant models of decision-making in discrimination tasks is examined… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
230
4

Year Published

2010
2010
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 138 publications
(246 citation statements)
references
References 250 publications
(471 reference statements)
12
230
4
Order By: Relevance
“…Thus, it could be argued that the pattern of bivariate correlations, the use of likelihood ratio bounds, and the addition of a noise distribution are distortions forced upon the signal detection framework to cope with a compression pattern that, in reality, largely reflects scale-usage phenomena. In line with this argument, the potentially distorting role of response processes is currently receiving increased attention in the signal detection literature (Benjamin, Diaz, & Wee, 2009;Mueller & Weidemann, 2008).…”
Section: Resultsmentioning
confidence: 89%
“…Thus, it could be argued that the pattern of bivariate correlations, the use of likelihood ratio bounds, and the addition of a noise distribution are distortions forced upon the signal detection framework to cope with a compression pattern that, in reality, largely reflects scale-usage phenomena. In line with this argument, the potentially distorting role of response processes is currently receiving increased attention in the signal detection literature (Benjamin, Diaz, & Wee, 2009;Mueller & Weidemann, 2008).…”
Section: Resultsmentioning
confidence: 89%
“…If there is some degree of trial-to-trial criterion variability (e.g. ; Benjamin et al, 2009), it's possible that some items which initially elicited a "no" response in the item recognition due to a high criterion were more likely to be recognized during the source test, eliciting a source retrieval instead of a guess, and so slightly greater than chance performance.…”
Section: Discussionmentioning
confidence: 99%
“…Such dependencies are common in many perceptual tasks and could have arisen for a number of reasons. One possibility is that Benjamin, Diaz, & Wee, 2007). We believe that the time has come to acknowledge the importance of decision noise in signal detection tasks and to begin moving beyond the simple application of SDT.…”
Section: Sequential Dependenciesmentioning
confidence: 99%
“…Recently, Benjamin, Diaz, and Wee (2007) noted that reasonable models of signal detection can be formed using decision noise instead of perceptual noise. Although decision noise models are difficult to distinguish from perceptual noise models, Benjamin et al ultimately concluded that decision-noise-only models were untenable.…”
Section: Notesmentioning
confidence: 99%